Integrated metabolomics and network pharmacology analysis to reveal the mechanisms of Wenshenyang decoction in the treatment of chronic kidney disease - Jin, Ge; Zhao, Zongjiang (Frontiers in Pharmacology, 2025)
BackgroundWenshenyang decoction (WSY) has been shown to have a considerable effect on restoring renal function and improving kidney Yang deficiency syndrome in patients with CKD. However, its mechanism remains unclear.AimsThis study aimed to integrated metabolomics and network pharmacology analysis combined with in vitro experiments to reveal the mechanisms.Materials and methodsPatients were selected from a clinical trial. LC-MS (Liquid chromatography-mass spectrometry) was used to investigate the differential metabolites and pathways. Spearman correlation analysis was performed between differential metabolites and clinical phenotypes. “Drug-component-differential metabolite” network was constructed to predict the core components and hub genes, and validated by molecular docking. On this basis, the effects of core components of WSY on the viability of Human Kidney-2 cells (HK-2) induced by doxorubicin (DOX) was detected by CCK-8, and RT-qPCR (Reverse transcription quantitative polymerase chain reaction) was used to detect the mRNA expression level of hub genes and related targets.Key findingsLC-MS detected 54 differential metabolites, of which 35 metabolites showed up regulated, and 19 decreased. Spearman analysis showed that the differential metabolites were correlated with the clinical phenotype. KEGG (Kyoto Encyclopedia of Genes and Genomes) enrichment analysis showed that WSY mainly affected linoleic acid metabolism, FcεRI signaling pathway, and unsaturated fatty acid biosynthesis. The “Drug-component-differential metabolite” network showed that the core components of WSY were quercetin, luteolin and kaempferol, and the hub genes were PTGS2, AKT1, MMP9, EGFR and MMP2. Molecular docking showed that they had good biological binding capacity. In vitro cell experiments further showed that quercetin, luteolin and kaempferol could significantly activate the cells and reduce the mRNA levels of PTGS2, AKT1, MMP9, EGFR, MMP2, and ANGPTL4, and increase the level of FGFR1, SIRT3 and the glucocorticoid receptor (GR).SignificanceWSY has multi-component and multi-target properties in the treatment of CKD kidney Yang deficiency syndrome, and its mechanism may be related to anti-inflammatory and anti-fibrotic effects. This study provides a methodological reference for the treatment of CKD.